Pemanfaatan Fitur-Fitur Whatsapp Business Untuk Meningkatkan Engagement Pelanggan dan Penjualan Bakso Aci Wocil - Nisa', I'anatun; Dewi, Dita Ovalia; Azhari, Hilda Inestya; Ningrum, Eri Rahma; Gunawan, Cameylia Salsabila; Sefia, Vema; Makrifaturrochmah, Makrifaturrochmah; Afandi, Frengki (Welfare : Jurnal Pengabdian Masyarakat, 2025)
In the digital era, the use of social media is very necessary in running a business. In the competitive culinary world, effective marketing is the key to attracting customer attention and increasing sales, especially in Micro, Small and Medium Enterprises (MSMEs). In this case, Bakso Aci Wocil utilizes the WhatsApp Business feature to boost its marketing. The aim of this service is to meet community needs through the use of digital technology, especially WhatsApp Business. Using the WhatsApp Business feature, Bakso Aci Wocil can increase customer engagement which leads to increased sales and welfare of business owners as well as meeting customer needs. This service method uses the service learning method to increase the involvement of students, customers and sales of Bakso Aci Wocil through the use of the WhatsApp Business feature. From the results of the dedication, it was found that the WhatsApp Business feature was able to increase the visibility and attractiveness of products in a competitive era and was able to reach customer accessibility and make it easier for customers to make transactions.